Service Learning in Higher Education: Evidence from Malaysia - le Salleh Hudin, Norlai; Osman, Juliana; Mohd Shokory, Suzyanty; Ab Wahid, Hariyati (International Journal of Engineering and Technology, 2018)
The conventional lecture teaching style designed by our education system is becoming less relevant in meeting the millennial studentsâ€™ learning necessities. Common lecture seems no longer adequate in developing an engaging and effective lesson for the graduates. For that reason, Malaysian Ministry of Education suggests SERVICE-LEARNING (SL) to be conducted to supplement student learning. Nevertheless, prior studies on SL effectiveness showed mixed results. Therefore, this study is conducted to understand and provide a detailed account of studentsâ€™ learning development in a higher education institution in Malaysia. By employing the qualitative methodology, 39 students participated in SL project were interviewed to understand studentsâ€™ learning development. The responses were transcribed verbatim and analyzed by using thematic analysis. The results revealed that knowledge and skills developed meaningfully through SL unlike in typical classroom setting where knowledge is expected to flow effectively from lecturers to students without real world experience or lasting impact. However, some students were found to understand the lesson slightly different from their peers. This research provides guidelines for course instructors to design SL in academic courses and improve student learning for the purpose of realizing Malaysian Education Blueprint 2013-2025.Â Â